2018
DOI: 10.1007/s00381-018-3803-0
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen therapy reduces astrogliosis and helps to recovery brain damage in hydrocephalic young rats

Abstract: The results suggest that hyperbaric treatment bettered the behavioral performance and offered benefits to the structures affected by the ventricular increase helping to recover the brain damages. In this way, the HBOT it can be considered an adjuvant therapy for the treatment of hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
2
0
5
Order By: Relevance
“…This may be due to lower peak levels of oral therapy than after parenteral administration. In other studies, hydrocephalic young rats treated with hyperbaric oxygen therapy performed better on behavioral tests than untreated rats, although there was no significant effect on ventricular dilation ( da Silva et al, 2018 ). Silva et al suggested that hyperbaric oxygen therapy may promote functional recovery of the CNS by inhibiting the activation of astrocytes and forming an extensive fibrillar network, in addition to its own antioxidant stress effect ( da Silva et al, 2018 ; Supplementary Table 1 ).…”
Section: Therapeutic Targeting Of Astrocytes For the Treatment Of Hyd...mentioning
confidence: 88%
“…This may be due to lower peak levels of oral therapy than after parenteral administration. In other studies, hydrocephalic young rats treated with hyperbaric oxygen therapy performed better on behavioral tests than untreated rats, although there was no significant effect on ventricular dilation ( da Silva et al, 2018 ). Silva et al suggested that hyperbaric oxygen therapy may promote functional recovery of the CNS by inhibiting the activation of astrocytes and forming an extensive fibrillar network, in addition to its own antioxidant stress effect ( da Silva et al, 2018 ; Supplementary Table 1 ).…”
Section: Therapeutic Targeting Of Astrocytes For the Treatment Of Hyd...mentioning
confidence: 88%
“…In the meantime, it has been revealed that HBO therapy showed promising effects in ameliorating neurological deficits after TBI [ 8 , 9 ]. In recent years, accumulating evidences indicated that HBO therapy not only promotes the repair of wounds, but also inhibits the excessive proliferation of glial cells, attributed greatly due to its distinctive character to inhibit scar formation, thereby facilitating the neurological repair on this basis [ 10 , 11 ]. However, the mechanisms through which HBO therapy exerts its neuroprotective role remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Os astrócitos são os principais responsáveis pelo reparo celular neuronal após lesão, e a GFAP é um marcador de astrócitos maduros. A presença dessas células a longo prazo leva a alterações estruturais (cicatrizes) e metabólicas no hipocampo, que barram a recuperação da função cognitiva (85,112). O processo de cicatrização neuronal não é completamente entendido, mas estima-se que os astrócitos possam se diferenciar em células progenitoras multipotentes (113).…”
Section: Discussionunclassified
“…A avaliação da histologia feita através do escore de lesão histológica intestinal apresentou valores médios de 0,20 para o grupo C, 0,96 para o grupo COHB1 e de 0, 85…”
Section: Graduação Histológica De Lesão Intestinalunclassified